Bacterial infection in Small Bowel and Multivisceral Transplantation – Literature Review - Weinfeld , Adriana; Gritti, Catiana Mitica; David, André Ibrahim; Silva, Ivan Leonardo Avelino França e; Abdala, Edson (Brazilian Journal of Transplantation, 2013)
The nature of infections after solid organ transplantation has changed significantly upon the advent of potent immunosuppressive regimens, the routine use of antibiotic prophylaxis and the advancement of microbiological diagnostic techniques. New pathogens are being identified in this population, including several with a significant antimicrobial resistance profiling. The after-transplant chronology of infections is set by the nature and intensity of individual epidemiological exposure and the immunosuppressant state of balance. The shortage of epidemiological studies on bowel and multivisceral post-transplant infections still keep their trend of being more a state of the art understanding than as science. The purpose of this study is to describe epidemiological data of intestine bacterial and multivisceral post- transplant infections. The most prevalent agents in the Small bowel and Multivisceral transplants were: Enterococcus spp, Staphylococcus spp, Streptococcus spp, Pseudomonas aeruginosa, Klebsiella pneumoniae, Escherichia coli, Enterobacter spp. The main sites of infection were the surgical site, intra-abdominal, blood, central venous catheter, urinary and respiratory systems. The identified risk factors were: acute rejection, high dose of immunosuppression, use of invasive devices, extensive surgery and reoperation, contaminated graft, previous infection and hospitalized patients in the pre- transplant period.